Use of an Implanted Sacral Nerve Stimulator to Restore Urine Voiding in Chronically Paraplegic Dogs. (29th November 2012) - Granger, N.; Chew, D.; Fairhurst, P.; Fawcett, J.W.; Lacour, S.P.; Craggs, M.; Mosse, C.A.; Donaldson, N.; Jeffery, N.D.
Abstract : Background: Loss of urinary control after spinal cord injury increases risk of urinary tract disease and is problematical for owners of affected dogs. Objectives: To design, implant, and test a sacral nerve stimulating device for controlling urine voiding in paraplegic dogs. Animals: Nine pet dogs with severe thoracolumbar spinal cord injury causing paraplegia, loss of hindquarter sensation, and incontinence for more than 3 months. The procedure was offered prospectively to owners of suitable candidates after the irreversibility of the incontinence had been ascertained. Methods: Open label clinical study. Surgically implantable electrode "books" were designed for insertion and retention of mixed sacral nerves. Sacral nerves were accessed via laminectomy and stimulated to test their ability to elicit detrusor contraction and then inserted into the electrode book, which was attached to a subcutaneously implanted, externally activated receiver. Results: In 8/9 dogs, S2 nerves elicited the largest increases in intravesicular pressure with minimum stimulation and were placed in electrode books. Voiding efficiency was >90% in 8 of the 9 implanted dogs. No important detrimental effects of the procedure were observed. Conclusions and Clinical Importance: This sacral nerve stimulating implant is a simple and apparently effective neuroprosthetic device that restores urine voiding in paraplegic dogs.